2023
DOI: 10.7759/cureus.37585
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Oral Manifestations in the Diagnosis of Severe Phenytoin-Induced Thrombocytopenia: A Rare Case

Abstract: Phenytoin is a commonly used anticonvulsant drug for the prophylaxis of generalized tonic-clonic seizures, partial seizures, and neurosurgery-related seizure prevention. Phenytoin-induced thrombocytopenia is a rare but life-threatening condition. Close monitoring of blood counts may be necessary for patients receiving phenytoin, as delay in diagnosis or withdrawal of the drug can be life-threatening. Clinical manifestations of phenytoin-induced thrombocytopenia are usually reported within one to three weeks af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…There have been reports of phenytoin-induced thrombocytopenia in patients who received phenytoin for the treatment or prevention of seizure disorders. Commonly, phenytoin-induced thrombocytopenia begins 1-90 days after administration, and the time of platelet recovery is 3-21 days after phenytoin discontinuation [4,[6][7][8][9][10][11][12][13].…”
Section: Figure 1: Relationship Between Platelet Count and Drug Admin...mentioning
confidence: 99%
“…There have been reports of phenytoin-induced thrombocytopenia in patients who received phenytoin for the treatment or prevention of seizure disorders. Commonly, phenytoin-induced thrombocytopenia begins 1-90 days after administration, and the time of platelet recovery is 3-21 days after phenytoin discontinuation [4,[6][7][8][9][10][11][12][13].…”
Section: Figure 1: Relationship Between Platelet Count and Drug Admin...mentioning
confidence: 99%
“…6 Currently, more studies are focusing on the issue of DIT, highlighting the severity of thrombocytope-nia in clinical practice. [7][8][9][10] A study has indicated that DIT occurs in 15% to 58% of patients admitted to intensive care units. 11 The primary challenge in the management of DIT is identifying the specific drug that contributed to thrombocytopenia.…”
mentioning
confidence: 99%
“…Currently, more studies are focusing on the issue of DIT, highlighting the severity of thrombocytopenia in clinical practice 7‐10 . A study has indicated that DIT occurs in 15% to 58% of patients admitted to intensive care units 11 .…”
mentioning
confidence: 99%